Mechanism of Share Transfer Through Court Decision for Shareholders in a State of Absence (Afwezigheid) - Effendy, Edrick Edwardina; Octaviara, Talia (Universitas Pelita Harapan, 2025)
There are many problems found in the civil aspect these days, which are diverse and complex, so comprehensive arrangements are needed to fulfil all civil rights in humans as one of the subjects of civil law. This research will specifically discuss the state of Afwezigheid as a shareholder of a limited liability company where the assets owned are in the form of shares. To carry out the civil rights of an absent person (Afwezig), a determination of Afwezigheid is required by the local District Court, which then appoints Balai Harta Peninggalan (BHP) as a Special Manager (Bewindvoerder) to carry out management of the absent person's assets. This research is a normative legal study using secondary data, applying statute approach, conceptual approach, and historical approach. The data were collected through literature review of books, laws, and regulations relating to the state of Afwezigheid and its position under the Civil Code and Law Number 40 of 2007 on Limited Liability Company. The findings indicate that the absence (Afwezigheid) of a shareholder must be established by a court ruling, with BHP managing the shareholder’s rights and assets. However, the lack of clear technical procedures for share transfer creates legal uncertainty in practice.